1991
DOI: 10.1111/j.1749-7345.1991.tb00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Spermatophore Generation Times inPenaeus setiferus, P. vannamei, andP. stylirostris

Abstract: Spermatophore development times were studied in three species of penaeid shrimp, Penueus setifcrus, P. vannumei, and P. stylirosrris. In the terminal ampoule, the progression of spermatophore formation occurred in 4 stages (I‐IV). The duration of each stage varied with species and ablation state. In unablated males, with spermatophores manually or electrically removed, structnrally complete spermatophores containing high numbers of morphologically normal sperm were formed in 2–4 days for P. vannamei, 4–6 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 19 publications
4
9
0
1
Order By: Relevance
“…Similar high mortality were observed by several researchers, [34][35][36] who studied the effect of unilateral and bilateral eyestalk ablation in decapod crustaceans. Furthermore, the pattern depicts that the increase was gradual during the progression of the CGE-1 administration at higher doses of CGE-1.…”
Section: Effect Of Cge-1 On Weight Gain Molt Frequency and Incrementsupporting
confidence: 85%
“…Similar high mortality were observed by several researchers, [34][35][36] who studied the effect of unilateral and bilateral eyestalk ablation in decapod crustaceans. Furthermore, the pattern depicts that the increase was gradual during the progression of the CGE-1 administration at higher doses of CGE-1.…”
Section: Effect Of Cge-1 On Weight Gain Molt Frequency and Incrementsupporting
confidence: 85%
“…Manually or electrically ejaculating the spermatophores can also remove melanin debris from the ampoules, and many studies use these methods to keep males in good condition in the absence of females. Indeed, most of these studies reported that, over extended time periods, spermatophores did not show deterioration (Leung-Trujillo and Lawrence, 1991;Alfaro, 1993;Alfaro and Lozano, 1993;Heitzmann and Diter, 1993;Pratoomchat et al, 1993;Alfaro, 1996;Pascual et al, 1998;Diaz et al, 2001;Ceballos-Vazquez et al, 2004). If the spermatophores are not evacuated (manually, electrically or through mating), they may become melanized in some individuals even within few days (as in Fig.·2) and subsequently hardened enough to prevent their ejaculation (Leung-Trujillo and Lawrence, 1987;Talbot et al, 1989;Perez-Velazquez et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In many decapod crustacean species, such as shrimps, lobsters and crabs, female reproduction is synchronized with the molt cycle and is thus cyclic by definition (Adiyodi, 1985;Nelson, 1991). The nature of the association between molt cycles and reproduction in decapod males is, however, not known, although a few clues do exist, all of them from penaeid shrimp: manually ejaculated Litopenaeus vannamei exhibited new pairs of spermatophores in their ejaculatory ducts (ampoules) only after molting (Heitzmann and Diter, 1993); a decline in spermatophore quality as the molt cycle progressed was observed in Fenneropenaeus indicus (Muthuraman, 1997); and naturally mating L. vannamei and L. setiferus were shown to be carrying new pairs of spermatophores a few days after mating within the same molt cycle that the mating had occurred (Leung-Trujillo and Lawrence, 1991). Whereas these are the only reported indications of an underlying periodic reproductive mechanism…”
Section: Introductionmentioning
confidence: 99%
“…The sperm count and the record of the proportions of live/dead and normal/abnormal sperm morphology estimations were made by macerating the spermatophores in 0.5 ml of distilled water and staining the river prawn sperm with eosin‐nigrosin in 1.5 ml Eppendorf tubes (Viana da Costa et al, ). The sperm count was assessed using a Neubauer camera and observed with an optical microscope at 10, 20, 40 and 100× magnification (Leung‐Trujillo & Lawrence, ). Sperm concentrations were reported as the number of sperm per microlitre (sperm/μl).…”
Section: Methodsmentioning
confidence: 99%